Reflections on Science at the Interface of the Islamization of Knowledge Debate - M. Zaki Kirmani (International Institute of Islamic Thought, 2011)
The author revisits the forty-year Islamization of knowledge debate in relation to science. He maintains that values and the worldview have an undeniable role in science and its multidimensional growth. He maintains that the role of values in science is no more controversial, and if some people still deny it, it may not be long before they will reverse and reframe their opinion on the relation between science and religion.